Marine Debris Management and Environmental Quality in Banggai Cardinalfish (Pterapogon kauderni Koumans, 1933) Habitat in Lalong Bay, Banggai Regency, Central Sulawesi - Ndobe, Samliok; Madinawati, Madinawati; Rukka, Andi Heryanti; Hermawan, Roni (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
Banggai Cardinalfish (BCF) habitat is found in protected waters, such as Lalong Bay, Banggai Regency. Banggai cardinalfish are associated with various biota such as sea urchins (especially Diadema setosum) which live close to coral reef, seagrass and mangrove ecosystems. The aim of this research was to analyze marine debris contamination in Banggai cardinalfish habitat in Lalong Bay. This research used a quadrat sampling method (2m x 2m) along 20 m-30 m line transects at 4 research stations. Based on the analysis, organic marine debris types comprised: medium-sized pieces of wood, wood chips, coconuts, coconut husks, leaves and fish carcasses. Inorganic marine debris types comprised glass bottles, tin cans, light bulbs, baby diapers, cooking oil bottles, mineral water bottles, plastic cups, plastic spoons, toothbrushes, buoys, plastic packaging, plastic baskets, lighters, ropes, fishing nets, styrofoam, rubber sandals, tires and other plastic debris. The average amount of debris was 17 items/m2, volume 0.13 m3, weight 1,251 gr/m2 at Station 1; 16.75 items/m2, volume 0.10 m3, weight 1,157 gr/m2; at Station 2; 20.5 items/m2, volume 0.04 m3, weight 2,341 gr/m2 at Station 3 26.3 items/m2, volume 0.07 m3, weight 1,895 gr/m2 at Station 4. Based on observations at these stations in the port, much of the BCF fish habitat was found to be exposed to marine debris due to high levels of human activity and a lack of waste management capacity.